Pembentukan Perusahaan Pesawat Terbang Indonesia sebagai Embrio Penerbangan Komersial dan Perkembangan Industri Pesawat Terbang di Indonesia 1949-1979 - Akhir Yuliana Setianingrum; Moch. Jurianto; Abdul Rivai Ras; Herlina Juni Risma Saragih; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The geographical spread of Indonesia's territory forces the government to have adequate modes of air transportation. If you review the economic context, having a national airline is an important thing to boost state finances or those who manage it. Managing airlines is one way for the government to get maximum mobility to conduct diplomacy with neighboring countries. So with the presence of Indonesian Airways, all these needs can be helped. The purposes of this paper are: First, to describe the history and development of Indonesian Airways. Second, to explain the fate of Indonesian Airways after the KMB was approved. Third, explain the development of Garuda Indonesia Airways and the development of the aviation industry in Indonesia. This research uses the method. The first is heuristics which is the stage of collecting relevant historical data or sources. Second, source criticism is the stage of reviewing the authenticity and credibility of the sources. Third, interpretation, namely interpreting facts that have been tested for truth. Fourth, historiography or historical writing, namely the delivery of a synthesis in the form of historical works. From this writing, it shows that 1. Indonesia was able to start an airline initiated by indigenous figures 2. After the KMB agreement took place, the airline returned to Indonesia and was merged with DAUM. And the management is getting better under the leadership of Wiweko Soepomo. Then did a joint venture with the Dutch KLM airline. 3. The next step is the gradual nationalization of the Dutch KLB, through the mechanism of buying shares from the KLM Group airline. After being officially owned by Indonesia, this opened the door for Indonesian aerospace and boosted the regional economy through airport enclavement